PENGARUH MODEL KOOPERATIF TIPE PICTURE AND PICTURE TERHADAP HASIL BELAJAR MATERI SISTEM PENCERNAAN MAKANAN DI SMP - Margaretha Madona; Eka Aryati; Yokhebed Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research  aimed to determine the effect of cooperative learning type picture and picture models on student learning outcomes in the material of food digestive system in class VIII SMP Santo Fransiskus Asisi Pontianak. The study was a quasy experimental research with a nonequivalent control group design. The sampling technique used was intact group, with class VIII A as experiment class and class VIII C as control class. The instrument was in the form of a multiple choice test with 20 items. The average learning outcomes of experimental class which was  16.22 while the average in control class was 15.03. The results of U-Mann-Whitney test showed that Z count (-2,84) <-Z table (-1,96), meaning that there were significant differences between the learning outcomes of students taught using cooperative learning type Picture and Picture model and conventional model. The effect size value obtained was 0,73 with a category of moderate and gave the effect of 26,73%. Keywords : Food Digestive System, Learning outcomes, Picture And Picture Cooperative